Aligning library instruction with the needs of basic sciences graduate students: a case study - O'Malley, Donna (Medical Library Association, 2012)
QUESTION: How can an existing library instruction program be reconfigured to reach basic sciences graduate students and other patrons missed by curriculum-based instruction? SETTING: The setting is an academic health sciences library that serves both the university and its affiliated teaching hospital. METHODS: The existing program was redesigned to incorporate a series of seven workshops that encompassed the range of information literacy skills that graduate students in the basic sciences need. In developing the new model, the teaching librarians made changes in pedagogy, technology, marketing, and assessment strategies. RESULTS: Total attendance at the sessions increased substantially in the first 2 years of the new model, increasing from an average of 20 per semester to an average of 124. Survey results provided insight about what patrons wanted to learn and how best to teach it. CONCLUSION: Modifying the program's content and structure resulted in a program that appealed to the target audience.